Cost‐effectiveness of aducanumab to prevent Alzheimer's disease progression at current list price - Pranay Sinha; Joshua A. Barocas (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction An estimated 6 million Americans have Alzheimer's disease (AD). Aducanumab was recently approved by the Food and Drug Administration despite the lack of clinical effectiveness data. Methods We developed a Markov state transition model of AD to estimate the cost effectiveness of aducanumab compared to standard of care (SOC) over a 5‐year time horizon for a cohort of persons aged 65 with mild AD. Outcomes included quality adjusted life years (QALYs), discounted costs, and incremental cost‐effectiveness ratios (ICERs). We performed sensitivity analyses to address uncertainty. Results Over 5 years, the incremental cost of aducanumab compared to SOC was $179,890. Aducanumab resulted in 0.47 QALYs gained compared to SOC. The ICER for aducanumab compared to SOC was $383,080/QALY. In threshold analysis, aducanumab became cost‐effective at $22,820/year. Discussion Aducanumab is not cost‐effective at the estimated price of $56,000 even under ideal circumstances in which it completely halts AD progression.